Perancangan dan Implementasi Encoder dan Decoder CRC-8 untuk Pendeteksian Error pada Transmisi Data antar Perangkat IoT - Donny Priyadi; Theophilus Wellem (STMIK Budi Darma, 2022)
Cyclic Redundancy Check (CRC) is a widely used error detection code in digital communication systems to detect errors in data transmitted between transmitter and receiver. With the development of Internet-of-Things (IoT) technology, where many devices communicate wirelessly, the application of error detection codes such as CRC is essential to obtain reliable communication. The computation of CRC can be implemented in hardware using a linear feedback shift register (LFSR) or in software with shift and bitwise exclusive OR (XOR) operations for polynomial division. Due to the frequent use of CRC in wireless communication for IoT, research for the design and implementation of CRC continues to this day. This study aims to design and implement the encoder and decoder of CRC-8 with generator polynomial 0x07 on IoT devices. Two algorithms for computing the CRC, namely bitwise computation using LFSR and another one using lookup tables, are implemented on the Arduino Uno R3 board. Two Arduino boards connected in serial were used to verify the encoder and decoder implementation in the data transmission and error detection process. The experiment results showed that the encoder could correctly calculate the CRC value from the input data. Furthermore, the computation using lookup tables takes about four times faster than the bitwise method but requires more memory. In contrast, the bitwise computation method requires less memory but slower computation time. When testing using input data of 128 characters, the bitwise-based encoder requires a computation time of 2.37 milliseconds, while the lookup table-based encoder utilizing a lookup table requires a computation time of 0.5 milliseconds. In the error detection test, the results demonstrated that the receiver could detect errors in the transmitted data with a percentage of 100%.